2018
DOI: 10.2478/ijm-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Balancing altruism and self-interest: GP and patient implications

Abstract: This paper explores how general practitioners (GPs) address potentially opposing motivations stemming from being altruistic and self-interested, and the implications for patients and GPs. The author finds that GPs address dual goals of patient care and profit generation. This can be challenging, while professional values (altruism) encourage a patient focus, business realities (self-interest) mandate other priorities. Viewing clinicians as altruistic in isolation of business needs is unrealistic, as is the not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…These concordances with several studies which highlighted that the concept of subordinating self-interest appears less appealing to students as a professional attribute [ 25 , 26 ]. A timely literature review by O’Riordan.C highlighted on how self-interest issues work as potent force in the modern world producing great stress on the practice of medicine [ 27 ]. Besides, Ginsburg, Regher and Lingard also reported that actions suggested by students for professional dilemmas were often framed by their own self-interest [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These concordances with several studies which highlighted that the concept of subordinating self-interest appears less appealing to students as a professional attribute [ 25 , 26 ]. A timely literature review by O’Riordan.C highlighted on how self-interest issues work as potent force in the modern world producing great stress on the practice of medicine [ 27 ]. Besides, Ginsburg, Regher and Lingard also reported that actions suggested by students for professional dilemmas were often framed by their own self-interest [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…So too, varying organizational challenges can be dealt with by continuous alignment of the organization. 22 , 24 , 30 , 46 , 58 , 78 , 84 …”
Section: Resultsmentioning
confidence: 99%
“…This appreciation of positive psychological benefits for altruism, was formerly taken as an ‘egoist’ or selfish motive [ 3 , 4 , 7 ]. There was an identified need for a balanced approach to altruism in some other studies [ 18 ] culminating in the more recent concept of ‘enlightened self-interest’ in altruism [ 8 ] which has a more balanced approach recognizing physician’s well-being as an advantage rather than a drawback. It promotes well-being of both the physicians and the patients as desirable [ 6 ].…”
Section: Discussionmentioning
confidence: 99%